Backstepping controller for speed loop of permanent magnet synchronous motors integrated with a time-varying disturbance load observer for Metro Nhon-Hanoi Station - Anh, An Thi Hoai Thu; Thai, Lam Quang; Minh, Pham Duc (Institute of Advanced Engineering and Science, 2025)
Urban rail systems offer the substantial potential for reducing environmental pollution, alleviating traffic congestion, ensuring safety, and maintaining punctuality. Nevertheless, the operation of urban rail demands substantial electrical energy, and saving energy solutions are crucial to exploiting the full advantages of electric trains. This paper proposes the replacement of traditional traction motors with permanent magnet synchronous motors (PMSMs) due to their superior efficiency, reduced power losses, and compact size compared to direct current (DC) motors or other asynchronous three-phase motors with equivalent power, developing a backstepping controller for the speed loop coupled with a load observer-time-varying disturbance (TVD). The simulation results were conducted in MATLAB/Simulink with parameters collected from the Nhon-Hanoi urban railway line, Vietnam, verifying the proposed algorithms' correctness and effectiveness.